Konsep Objek Kajian Pendidikan Global dan Multikultural di Era Digital : The Concept of the Object of Study in Global and Multicultural Education in the Digital Era - Vamiati, Sri (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
Globalization is a process that integrates individuals as citizens of the world. Developing awareness in interacting and communicating among various ethnic, cultural, and religious backgrounds has become an essential need for every individual. This needs to be realized through an educational framework oriented towards global and multicultural realities to wisely face differences and the dynamics of life. This article aims to examine the concept of global education as a systematic effort to build students' awareness of their connection to global phenomena, as well as to analyze multicultural education as a means of fostering understanding and respect for cultural, racial, ethnic, and religious diversity. The method used is qualitative literature review with a comprehensive analysis of relevant studies. The results of the study indicate that the focus of global and multicultural education includes self-awareness as part of an interconnected world society, an egalitarian attitude towards proportional gender equality, respect for human values, and an awareness of the importance of religious moderation.